Comparison Of SINR In FemtoCell & MacroCell Network In MacroCell Environment (International Journal of Engineering and Computer Science, 2013)
Femtocells (HeNB) are deployed within macrocell coverage area to increase performance of indoor user. In order to cover, all indoor users, HeNBs make a network, known as femtocell network. Since, HeNBs use same spectrum, they are causing interference on both MeNB users (MUE) and among HeNB users (HUE). The performance of the femtocell network depends on the SINR of HUEs of respective HeNBs, which eventually depends on the interference produced on it. In order to improve the performance, we need to minimize the interferences among them. In this paper, we first study the SINR performance of HUEs in presence macrocell. We also analyze the outage probability in femtocell network. Finally, consider the power consumption of femtocell network.